Transseptal transcatheter mitral valve implantation versus redo surgical mitral valve replacement for degenerated mitral bioprostheses. (25th November 2020) - Fuchs, A; Iung, B; Nguyen, C; Carrasco, J.L; Cimadevilla, C; Kerneis, C; Eugene, M; Ghodhbane, W; Ducrocq, G; Brochet, E; Provenchere, S; Vahanian, A; et al.
Abstract: Background: The growing use of surgical bioprostheses raises concerns about a future reoperation for bioprosthesis degeneration. There are few data on outcome after transcatheter mitral valve-in-valve implantation (TMVI) compared with redo surgical mitral valve replacement (SMVR). Purpose: To compare the feasibility, safety and outcomes of TMVI versus SMVR for degenerated mitral bioprosthesis in high-risk patients. Methods: In our institution, 52 patients underwent TMVI by transseptal approach and 33 SMVR for degenerated mitral bioprosthesis. The composite endpoint of event-free survival included cardiovascular mortality, stroke, major bleeding, hospitalization for heart failure or mitral valve reintervention. Results: Mean age and EuroSCORE II were higher in TMVI group vs. SMVR group (age 63±21 years vs. 51±15 years, p=0.002; EuroSCORE II 12.5±12.2% vs. 6.2±3.3%, p=0.001) (Table). In-hospital mortality was 3.8% after TMVI vs. 3.0% after SMVR (p=1.0). Median follow-up was 2.2 years. At 5 years, survival was 69.7±9.4% after TMVI vs. 86.6±7.6% after SMVR (p=0.10) and event-free survival was lower after TMVI (40.1±9.9% vs 78.7±8.8% respectively, p=0.003) (Figure). In multivariate analysis, older age (p=0.02), neurologic history (p=0.05) and non-elective procedure (p<0.0001) were associated with lower event-free survival, while TMVI vs. SMVR was no longer significant (p=0.17). At last follow-up, 84% patients from TMVI group and 78% from SMVR group were NYHA I-II class. Mean mitral valve gradient and pulmonary artery systolic pressure were respectively 6.8±2.5 mmHg and 45±14 mmHg in TMVI group, and 4.8±2.0 mmHg and 37±11 mmHg in SMVR group. Conclusion: TMVI is an alternative to SMVR in high-risk patients with degenerated mitral bioprosthesis. Comparison of mid-term results of the two techniques must take into account the differences in patient characteristics. Funding Acknowledgement: Type of funding source: None